Analisis Persepsi Kemudahan Dan Persepsi Keamanan Dalam Mempengaruhi Minat Menggunakan QRIS Livin’ By Mandiri Di Kota Padang - Trianita, Mery; ., Irda; kamela, Ice; ., Yuhelmi; Ahmad, Irfan (CV. ITTC INDONESIA, 2025)
Advancements in information and communication technology have transformed various aspects of daily life, including how people conduct financial transactions. One of the rapidly growing innovations in Indonesia’s digital payment system is QRIS (Quick Response Code Indonesian Standard), which is also integrated into the Livin’ by Mandiri application. However, the suboptimal use of QRIS in Padang City raises questions regarding the factors influencing public interest in adopting this payment method. This study aims to analyze the effect of perceived ease of use and perceived security on behavioral intention to use QRIS through the Livin’ by Mandiri application in Padang City. The researchers employed a quantitative approach using purposive sampling technique, involving 60 respondents who met the criteria: Bank Mandiri customers, users of the Livin’ by Mandiri application, and individuals over 17 years of age. Data were analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The analysis included convergent validity and discriminant validity tests using the Fornell-Larcker criterion and cross loadings, as well as R-Square and Structural Model Assessment (SMA) to evaluate causal relationships between latent variables. The results revealed that perceived ease of use does not significantly influence the intention to use QRIS through Livin’ by Mandiri in Padang City, thus rejecting the proposed hypothesis. Conversely, perceived security significantly affects the intention to use the service. This indicates that data protection and prevention of misuse are critical factors driving users' intention to adopt QRIS through the Livin’ by Mandiri application.